Demonglass - Hawkins, Rachel, 1979- (Hawkins, Rachel, 1979- Hex Hall novel., 2011)
After learning that she is capable of dangerous magic, Sophie Mercer goes to England with her father, friend Jenna, and Cal hoping to have her powers removed, but soon she learns that she is being hunted by the Eye--and haunted by Elodie.